2009
DOI: 10.1590/s1517-83822009000100033
|View full text |Cite
|
Sign up to set email alerts
|

EMJH medium with 5-fluorouracil and nalidixic acid associated with serial dilution technique used to recover Leptospira spp from experimentally contaminated bovine semen

Abstract: Bovine semen experimentally contaminated with Leptospira santarosai serovar Guaricura was submitted to the modified EMJH medium with 5-fluorouracil (300mg/L) and nalidixic acid (20mg/L), named as "selective medium" and using the serial dilution technique, in order to evaluate the percentage of recovery of the added microorganism. The selective EMJH medium was found with higher percentage of recovery of leptospiras and minor losses of samples due to contamination with opportunistic microorganisms than the non-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…It is important to highlight that the sample (bovine semen) was experimentally spiked, what may have influenced the results (Miraglia et al . ). Regarding 5‐FU associated with serial dilution, a similar rate to that observed in the present study (3·8%) was reported on urine of naturally infected goats (Lilenbaum et al .…”
Section: Resultsmentioning
confidence: 97%
“…It is important to highlight that the sample (bovine semen) was experimentally spiked, what may have influenced the results (Miraglia et al . ). Regarding 5‐FU associated with serial dilution, a similar rate to that observed in the present study (3·8%) was reported on urine of naturally infected goats (Lilenbaum et al .…”
Section: Resultsmentioning
confidence: 97%
“…The inoculum was prepared by diluting a seven-day old Leptospira culture with fresh Ellinghausen-McCullough-Johnson-Harris (EMJH) broth to reach a bacterial density of 2 × 10 6 CFU/mL by using a spectrophotometer at the 420 nm wavelength. The optical density (OD) of 0.32 at 420 nm approximately corresponded to 1 × 10 8 CFU/mL (16). The OD of 0.064 was approximately equal to 2 × 10 7 CFU/mL, and a 10-fold dilution was performed to reach a leptospiral density of 2 × 10 6 CFU/mL.…”
Section: Methodsmentioning
confidence: 99%
“…Throughout the experiment clinical monitoring of animals was done. ), termed 'selective medium' (Miraglia et al, 2009), using the serial dilution technique, in order to evaluate the percentage recovery of the added micro-organism. These cultures were incubated at an average temperature of 29 uC.…”
Section: Methodsmentioning
confidence: 99%